PtRu-based nanocage catalyst based on chromium regulation and preparation method and application thereof

CN122406303BActive Publication Date: 2026-10-23HEFEI UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610847012.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-12
Publication Date
2026-10-23
Estimated Expiration
2046-06-12

AI Technical Summary

Technical Problem

但在碱性电解环境中,HER需经历额外的水分子解离步骤,其反应动力学明显慢于酸性体系,导致传统Pt基催化剂的催化效率显著下降

Benefits of technology

[0024]1、本发明提供了一种基于非贵金属铬协同调控的PtRu纳米笼催化剂制备方法,通过在含氢气氛中进行热还原处理,使Pt、Ru前驱体转化为金属活性组分并形成多金属协同结构,有效调节催化剂的电子结构与表面活性位点分布,从而在降低贵金属用量的同时提升催化反应活性。该方法工艺流程简洁,条件易于控制,具有良好的可重复性及产物一致性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122406303B_ABST
    Figure CN122406303B_ABST
Patent Text Reader

Abstract

The application discloses a PtRu-based nanocage catalyst based on chromium regulation and a preparation method and application thereof, and the method comprises the following steps: (1) introducing a ruthenium precursor, a platinum precursor and a chromium precursor into a ZIF-8 metal organic framework material, and forming a multi-metal precursor / ZIF-8 composite with a hollow porous nanocage structure through reaction adsorption loading; (2) performing heat treatment on the multi-metal precursor / ZIF-8 composite in a hydrogen-containing reducing atmosphere to obtain a PtRuCrZnO intermediate; and (3) removing ZnO in the PtRuCrZnO intermediate by using an acidic etching solution to obtain the PtRu-based nanocage catalyst. The catalyst obtained by the application is particularly suitable for an AEMWE system, and provides a scalable technical solution for constructing a low-noble-metal-loading and high-efficiency water electrolysis hydrogen production catalyst material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of anion exchange membrane water electrolysis technology, specifically to chromium-controlled PtRu-based nanocage catalysts, their preparation methods, and applications. Background Technology

[0002] Alkaline anion exchange membrane water electrolysis (AEMWE) combines the technological advantages of traditional alkaline electrolysis and proton exchange membrane electrolysis, showing great application potential in reducing system costs and improving device safety. However, the practical application of the current AEMWE system is still limited by the performance of electrode catalytic materials, especially the difficulty in balancing the efficiency and economy of the cathode hydrogen evolution catalyst.

[0003] In existing technologies, platinum (Pt) is widely considered a highly efficient catalyst for the hydrogen evolution reaction (HER) due to its suitable hydrogen adsorption energy. However, in alkaline electrolysis environments, HER requires an additional water molecule dissociation step, and its reaction kinetics are significantly slower than in acidic systems, leading to a significant decrease in the catalytic efficiency of traditional Pt-based catalysts. Furthermore, the limited reserves and high cost of Pt resources make it difficult for highly loaded Pt catalysts to meet the cost control requirements of large-scale commercial applications.

[0004] Therefore, developing an electrocatalytic material that is easy to prepare, requires low amounts of precious metals, and can maintain excellent HER activity under alkaline conditions has become a key technical issue for promoting the further development of AEMWE technology. Summary of the Invention

[0005] This invention aims to provide a chromium-modified PtRu-based nanocage catalyst, its preparation method, and its applications. By introducing chromium (Cr) into the PtRu bimetallic system to construct a multi-metal synergistic structure, the electronic structure and active site environment of the catalyst can be modulated, thereby improving the performance of alkaline HER while reducing the amount of precious metal platinum used. The catalytic material can be applied to the cathode of AEMWE, providing a feasible technical solution for developing highly active, low-precious-metal-loaded water electrolysis hydrogen production catalysts.

[0006] In one aspect of the present invention, a method for preparing a chromium-controlled PtRu-based nanocage catalyst is proposed. According to an embodiment of the present invention, the method includes the following steps:

[0007] (1) Ruthenium precursor, platinum precursor and chromium precursor are introduced into ZIF-8 (zeolite imidazole ester framework material-8) metal-organic framework material, and a hollow porous nanocage structure multi-metal precursor / ZIF-8 complex is formed by reaction adsorption loading.

[0008] (2) The multi-metal precursor / ZIF-8 complex was heat-treated in a hydrogen-containing reducing atmosphere to reduce Pt and Ru metal ions to the metallic state in situ, while Cr still exists in the form of oxides. At the same time, ZIF-8 decomposed to release zinc ions and formed a transition metal complex structure with Pt, Ru and Cr to obtain the PtRuCrZnO intermediate.

[0009] (3) The ZnO in the PtRuCrZnO intermediate was removed by acid etching solution, and the structure was reconstructed to obtain a PtRu-based nanocage catalyst with a hollow porous cage morphology.

[0010] In addition, the preparation method of the chromium-controlled PtRu-based nanocage catalyst according to the above embodiments of the present invention may also have the following additional technical features:

[0011] In some embodiments of the present invention, in step (1), the ZIF-8 metal-organic framework material is prepared as follows: zinc nitrate hexahydrate solution, 2-methylimidazole solution, and hexadecyltrimethylamine bromide solution are stirred and mixed evenly, and then allowed to stand to obtain a ZIF-8 suspension. ZIF-8 has a regular three-dimensional porous framework structure, high specific surface area, and abundant pore environment, which can promote the uniform adsorption and dispersion of metal precursors such as Pt, Ru, and Cr on its framework surface and in its pores, which is beneficial to the formation of a uniform multi-metal active structure during subsequent heat treatment. In addition, the ZIF-8 framework contains Zn element. During hydrothermal treatment, Zn can undergo Kirkendall effect with Pt, Ru, and Cr to form a hollow porous structure. At the same time, ZnO is selectively removed during subsequent acid etching. This process not only helps to increase the specific surface area and active site exposure of the catalyst, but also improves the mass transfer and diffusion performance of reactants and products during the reaction.

[0012] In some embodiments of the present invention, the mass ratio of zinc nitrate hexahydrate, 2-methylimidazole, and hexadecyltrimethylamine bromide is (0.3-0.4):(5-6):(0.016-0.018); the stirring speed is 350-450 rpm, the stirring time is 5-10 min, and the settling time is 2-3 h.

[0013] In some embodiments of the present invention, step (1) is specifically as follows: a mixed solution of ruthenium precursor, platinum precursor and chromium precursor is added to a ZIF-8 suspension, stirred, hydrothermally treated, centrifuged and dried to obtain the composite. The ruthenium precursor, platinum precursor and chromium precursor are ruthenium chloride, chloroplatinic acid and chromium chloride, respectively. The metal precursor mainly provides the metal source and can undergo Kirkendall effect ion exchange with the Zn-containing ZIF-8 template, forming a hollow porous nanocage structure during the hydrothermal treatment process.

[0014] The mass ratio of the ruthenium precursor, platinum precursor, chromium precursor, and ZIF-8 metal-organic framework material is (8-12):(0.5-5):(0.5-10):(16-18); and / or, the reaction temperature is 50-80 °C, the reaction time is 2-4 h; the stirring speed is 350-450 rpm; the centrifugation speed is 8000-12000 rpm; the drying temperature is 60-70 °C, and the drying time is 3-5 h. A reaction temperature of 50-80 °C is considered relatively mild; excessively high temperatures may cause structural collapse during the reaction.

[0015] In some embodiments of the present invention, in step (2): the volume ratio of hydrogen to inert gas in the hydrogen-containing reducing atmosphere is (5%–10%):(90%–95%); and / or, the heat treatment temperature is 300–350 °C, the calcination time is 2–3 h, and the heating rate is 5–10 °C / min. In the hydrogen-containing reducing atmosphere, hydrogen mainly acts as a reducing gas to promote the conversion of Pt, Ru, and Cr metal precursors to the metallic state, thereby forming a multi-metallic component with catalytic activity. When the temperature is below 300 °C, Pt, Ru, and Cr precursors are difficult to fully reduce. When the temperature is above 350 °C, metal particles are prone to sintering and agglomeration, resulting in a decrease in specific surface area and a reduction in active sites. At the same time, it may cause the collapse of the hollow structure, thereby affecting the electrochemical performance of the catalyst.

[0016] In some embodiments of the present invention, in step (3), the acid etching solution is a 0.5–1 mol / L hydrochloric acid solution, and the etching time is 20–40 min. The acid etching process reduces the coverage of inactive ZnO components on the catalyst surface, which is beneficial for increasing the exposure of active sites and further optimizing the pore structure and specific surface area of ​​the material.

[0017] In another aspect of the present invention, the present invention provides a method for preparing PtRuCr nanocage catalysts based on chromium regulation of PtRu nanocage catalysts as described above.

[0018] In addition, the PtRuCr nanocage catalyst according to the above embodiments of the present invention may also have the following additional technical features:

[0019] In some embodiments of the present invention, the PtRuCr nanocage catalyst has a hollow porous cage structure and contains multi-metal synergistic active sites formed by Pt, Ru, and Cr elements. During hydrothermal treatment, the added metal precursor can undergo Kirkendall effect ion exchange with the Zn-containing ZIF-8 template, thereby forming a hollow porous nanocage structure.

[0020] In another aspect of the present invention, the present invention proposes the application of chromium-controlled PtRu-based nanocage catalysts in alkaline anion exchange membrane water electrolysis.

[0021] Furthermore, the application of the chromium-controlled PtRu-based nanocage catalyst in alkaline anion exchange membrane water electrolysis according to the above embodiments of the present invention may also have the following additional technical features:

[0022] In some embodiments of the present invention, the PtRuCr nanocages are used to prepare electrode materials for the hydrogen evolution reaction at the cathode of water electrolysis. This is because the PtRuCr nanocages have a hollow porous structure and a large specific surface area, which provides abundant electrocatalytic active sites and facilitates the rapid transport of electrolyte and reaction intermediates on the catalyst surface, thereby improving the efficiency of the hydrogen evolution reaction.

[0023] Compared with the prior art, the beneficial effects of the present invention are:

[0024] 1. This invention provides a method for preparing a PtRu nanocage catalyst based on the synergistic regulation of non-precious metal chromium. Through thermal reduction treatment in a hydrogen-containing atmosphere, Pt and Ru precursors are converted into metallic active components and form a multi-metal synergistic structure, effectively regulating the electronic structure and surface active site distribution of the catalyst, thereby improving catalytic activity while reducing the amount of precious metals used. This method has a simple process flow, easily controllable conditions, and good reproducibility and product consistency.

[0025] 2. This invention employs a selective acid etching process to remove template-derived ZnO components, significantly increasing the specific surface area of ​​the catalyst and the exposure of active sites, while reducing the masking effect of inactive components on active sites, thereby improving the electrochemical reactivity and operational stability of the material.

[0026] 3. This invention utilizes the ZIF-8 metal-organic framework as a structure-guided template to uniformly distribute various metal precursors in its channels and framework. After thermal conversion, a nanocatalyst with a three-dimensional porous hollow structure is formed. This structure can promote the activation of water molecules and the desorption process of hydrogen, thereby improving the kinetic performance of alkaline hydrogen evolution reaction and increasing the overall electrocatalytic efficiency.

[0027] 4. This invention modulates the electronic structure and coordination environment of the PtRu system by introducing the non-precious metal Cr. Pt provides suitable hydrogen adsorption / desorption capacity, Ru promotes the dissociation of water molecules under alkaline conditions, and the introduction of Cr can further regulate the electronic structure and local coordination environment of the catalyst surface, improve the adsorption energy of reaction intermediates, significantly reduce the proportion of precious metals used while maintaining high catalytic activity, and effectively improve the kinetic performance and long-term operational stability of the catalyst in alkaline hydrogen evolution reaction. Attached Figure Description

[0028] Figure 1 This is a transmission electron microscope image of ZIF-8 obtained in step (1) of Embodiment 1 of the present invention;

[0029] Figure 2 In the diagram, a is a transmission electron microscope image of the PtRuCr@ZIF-8 precursor obtained in step (2) of Example 1 of the present invention, b is a transmission electron microscope image of the PtRuCr@ZIF-8 precursor obtained in step (2) of Example 2 of the present invention, and c is a transmission electron microscope image of the PtRuCr@ZIF-8 precursor obtained in step (2) of Example 3 of the present invention.

[0030] Figure 3 In the diagram, a is a transmission electron microscope image of the PtRu-based nanocage catalyst obtained in step (4) of Example 1 of the present invention, b is a transmission electron microscope image of the PtRu-based nanocage catalyst obtained in step (4) of Example 2 of the present invention, and c is a transmission electron microscope image of the PtRu-based nanocage catalyst obtained in step (4) of Example 3 of the present invention.

[0031] Figure 4 The PtRu obtained in step (4) of Embodiment 1 of the present invention 17 Cr 2.5 The elemental mapping diagram of the nanocage using EDS (energy-dispersive X-ray spectroscopy), where a represents PtRu. 17 Cr 2.5 High-resolution images of nanocages: b is the elemental mixing image, c corresponds to the mapping image of Pt, d corresponds to the mapping image of Ru, e corresponds to the mapping image of Cr, and f corresponds to the mapping image of Zn.

[0032] Figure 5 The PtRuCrZnO intermediate obtained in step (3) and the PtRu obtained in step (4) of Embodiment 1 of the present invention are... 17 Cr 2.5 X-ray diffraction pattern of nanocages;

[0033] Figure 6 The PtRu obtained in step (4) of Embodiment 1 of the present invention 17 Cr 2.5 X-ray photoelectron spectra of nanocages, specifically, a is the high-resolution scanning spectrum of Ru 3p, b is the high-resolution scanning spectrum of Pt 4f, and c is the high-resolution scanning spectrum of Cr 2p.

[0034] Figure 7 In the diagram, a is a comparison of the electrochemical performance of the PtRu-based nanocage catalysts prepared in Examples 1-3 of this invention, and b is a comparison of the electrochemical performance of the PtRu-based nanocage catalysts prepared in Example 1 of this invention. 17 Cr 2.5 Nanocage, PtRu10 Comparison of electrochemical performance of nanocages, commercial platinum-carbon (Pt / C) and ruthenium-carbon (Ru / C);

[0035] Figure 8 In the example, 'a' represents PtRu in the application of this invention. 17 Cr 2.5 Nanocage, PtRu 10 AEMWE performance graphs of nanocages and commercial Pt / C, where b represents PtRu 17 Cr 2.5 Comparison of battery voltages between nanocages and commercial Pt / C at different current densities. Detailed Implementation

[0036] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0037] The centrifuges used in the following examples were Anke (Anting) TGL (tabletop high-speed refrigerated centrifuge)-10B manufactured by Shanghai Anting Scientific Instrument Factory; the magnetic stirrers were MS-MS-10 multi-head magnetic stirrers manufactured by Shanghai Kunquan Biotechnology Co., Ltd.; the tube furnaces were OTF-1200X manufactured by Hefei Kejing Materials Technology Co., Ltd.; and the transmission electron microscopes were JEOL (Japan Electronics Corporation)-F2010 manufactured in Japan. The pharmaceuticals used in the following examples were used directly after purchase without any processing.

[0038] Example 1

[0039] The preparation method of chromium-regulated PtRu-based nanocage catalysts includes the following steps:

[0040] (1) Weigh 0.7252 g of zinc nitrate hexahydrate and add it to 25 mL of deionized water. Stir at approximately 400 rpm for about 10 min at room temperature using a magnetic stirrer until it is completely dissolved to form a homogeneous and transparent solution, which is denoted as solution A. Separately, take 11.3504 g of 2-methylimidazole and 0.035 g of cetyltrimethylammonium bromide (CTAB) and add them to 175 mL of deionized water. Stir at the same stirring speed at room temperature for about 10 min until the solid is completely dissolved to obtain a homogeneous solution, which is denoted as solution B. Subsequently, under continuous rapid stirring, add solution A to solution B all at once and continue to react at a stirring speed of approximately 400 rpm for 5 min to promote sufficient contact and homogeneous mixing of the precursors. After the reaction is completed, transfer the resulting mixture to a constant temperature environment of 25 °C and allow it to stand for 3 h to age. Finally, a ZIF-8 suspension is obtained, and its transmission electron microscopy image is shown below. Figure 1 As shown.

[0041] (2) Take 8 mL of the ZIF-8 suspension prepared in step (1) and centrifuge at 12000 rpm for 10 min to separate the solid product. Then, wash twice with methanol (12000 rpm, 4 min each time) to remove unreacted substances and impurities. Redisperse the obtained precipitate in 3 mL of deionized water and sonicate it to form a uniform dispersion system. Then transfer it to a 20 mL polytetrafluoroethylene-lined reactor and denote it as solution C. Weigh 10 mg of ruthenium chloride, 1 mg of chloroplatinic acid and 2 mg of chromium chloride respectively, add them to a mixed solvent composed of 2 mL of deionized water and 1 mL of methanol, and sonicate until completely dissolved to obtain a homogeneous metal precursor solution, denoteed as solution D. Under magnetic stirring (about 400 rpm), slowly add solution D to solution C and continue stirring for 30 min to promote the complete ion exchange between the metal precursor and the zinc element in ZIF-8 to form a hollow porous nanocage structure. Then place the reaction system at 80 °C for hydrothermal treatment for 2 h. After the reaction was completed, the product was collected by centrifugation at 8000 rpm for 1 min and dried in a vacuum environment at 60 ℃ for 3 h to obtain the chromium-containing PtRuCr@ZIF-8 precursor material.

[0042] (3) The PtRuCr@ZIF-8 composite material obtained in step (2) was placed in a ceramic boat and heated to 300 °C at a heating rate of 10 °C / min under a 5% H2 / Ar atmosphere. The mixture was then calcined for 2 h to obtain the PtRuCrZnO intermediate.

[0043] (4) Weigh 5 mg of the PtRuCrZnO intermediate obtained in step (3), add 1 mL of 0.5 mol / L hydrochloric acid solution, soak for 20 min, centrifuge (10000 rpm, 2 min), wash with deionized water and centrifuge (10000 rpm, 2 min) to obtain PtRu 17 Cr 2.5 Nanocage catalyst.

[0044] Depend on Figure 4 As shown, for PtRu 17 Cr 2.5 EDS mapping analysis of the nanocage catalyst showed that Pt, Ru, Cr, and trace Zn were uniformly distributed on the nanocage, proving that Cr was successfully introduced into the PtRu nanocage catalyst.

[0045] Weigh 1 mg PtRu 17 Cr 2.5 The nanocage catalyst sample was added to 5 mL of nitric acid solution and transferred to a reaction vessel for hydrothermal digestion at 160 °C for 10 h. After the reaction, the resulting solution was removed and further dissolved in 15 mL of aqua regia. The solution was then sonicated until completely dissolved to form a homogeneous solution. Subsequently, the solution was diluted to a predetermined volume using deionized water and finally analyzed by inductively coupled plasma mass spectrometry (ICP-MS) to determine the content of each element in the sample. As shown in Table 1, the mass fraction of Pt was only 3.9%, the mass fraction of Ru was 36.2%, and the mass fraction of Cr was 2.7%, indicating the successful preparation of a Cr-regulated PtRu-based nanocage catalyst.

[0046] Table 1 PtRu 17 Cr 2.5 Metal mass percentages of Pt, Ru, Cr and Zn in nanocages

[0047]

[0048] Depend on Figure 5 As shown, PtRu 17 Cr 2.5 The nanocages contained only the Ru crystalline phase and no Pt crystalline phase was observed. Furthermore, the characteristic peaks of ZnO disappeared after acid washing. These results are in high agreement with the EDS and ICP-MS characterization results.

[0049] Example 2

[0050] The preparation method of the chromium-regulated PtRu-based nanocage catalyst differs from Example 1 only in that, in step (2), the mass of RuCl3 is 10 mg, the mass of H2PtCl6 is 1 mg, and the mass of CrCl3 is 1 mg. All other steps and parameters are the same as in Example 1. This embodiment ultimately yields PtRu... 10 Cr nanocage composite material.

[0051] Example 3

[0052] The preparation method of the chromium-regulated PtRu-based nanocage catalyst differs from Example 1 only in that, in step (2), the mass of RuCl3 is 10 mg, the mass of H2PtCl6 is 1 mg, and the mass of CrCl3 is 4 mg. All other steps and parameters are the same as in Example 1. This embodiment ultimately yields PtRu... 10 Cr4 nanocage composite material.

[0053] Comparative Example 1

[0054] A method for preparing a PtRu-based nanocage catalyst differs from Example 1 only in that: in step (2), the mass of RuCl3 is 10 mg, the mass of H2PtCl6 is 1 mg, and no additional CrCl3 is added; all other steps and parameters are the same as in Example 1. This embodiment ultimately yields PtRu... 10 Nanocage catalyst.

[0055] Depend on Figure 2 As shown, even with the addition of different masses of CrCl3, the morphology of the synthesized material did not change significantly after hydrothermal calcination and remained a nanocage structure.

[0056] Depend on Figure 3 As shown, the PtRu-based nanocage catalysts prepared in Examples 1-3 have complete cage structures.

[0057] Depend on Figure 6 As shown, PtRu prepared in Comparative Example 1 10 Compared to nanocages, PtRu 17 Cr 2.5 The binding energies of Ru 3p and Pt 4f in the nanocage both underwent positive shifts, indicating that in PtRu 17 Cr 2.5 Doping Cr ions into nanocages can modulate the electronic structure of Ru and Pt. Optimized PtRu 17 Cr 2.5 The electronic structure of nanocages can optimize their adsorption strength for HER reaction intermediates, thereby improving the HER performance of Ru and Pt.

[0058] Weigh out 1 mg of PtRu17 Cr 2.5 Nanocage, PtRu 10 Cr nanocages, PtRu 10 Cr4 nanocages, PtRu 10 Nanocages were added to 990 μL of isopropanol and 10 μL of Nafion (perfluorosulfonic acid polymer solution) along with 1.5 mg of carbon black, and sonicated for at least 30 min to ensure uniform catalyst dispersion. Then, 1 mg of Pt / C and Ru / C were added to 990 μL of isopropanol and 10 μL of Nafion, respectively, and sonicated for at least 30 min to ensure uniform catalyst dispersion, serving as control samples for electrochemical performance testing. A 10 μL droplet of the dispersion was then placed on a glassy carbon electrode. After drying, the electrode was used as the working electrode for HER performance testing. The reference electrode was Hg / HgO, and the counter electrode was a carbon rod electrode. Electrochemical tests were performed in a 1 mol / L KOH electrolyte saturated with H2.

[0059] like Figure 7 As shown, PtRu 17 Cr 2.5 The activity of the nanocage is significantly higher than that of other catalysts, at a current density of 10 mA / cm². 2 At that time, the overpotential was only 25 mV. PtRu 17 Cr 2.5 The enhanced catalytic activity of the nanocage is due to the introduction of Cr, which increases the electrochemical specific surface area of ​​the catalyst and exposes more active sites. In addition, there is a synergistic effect among the Pt, Ru and Cr multi-metal components. Pt can provide suitable hydrogen adsorption / desorption capacity, Ru is conducive to promoting the dissociation process of water molecules under alkaline conditions, and the introduction of Cr can further regulate the electronic structure and local coordination environment of the catalyst surface, improve the adsorption energy of reaction intermediates, and thus accelerate the kinetics of alkaline hydrogen evolution reaction.

[0060] Application examples

[0061] A water electrolysis method using an alkaline anion exchange membrane includes the following steps:

[0062] The PtRu prepared in Example 1 were respectively 17 Cr 2.5 Nanocage catalyst, PtRu 10 Nanocage catalyst and commercially available Pt / C are respectively sprayed onto one side of the anion exchange membrane as cathode materials. This anion exchange membrane (AEMemr®-PAW-1-60) is a high-strength, high-alkali-resistant anion exchange membrane based on a polyaromatic backbone, possessing advantages such as high strength and high ionic conductivity. PtRu 17 Cr 2.5 Nanocage catalyst, PtRu 10The loading of nanocage catalyst and commercial Pt / C noble metal Pt on anion exchange membranes were 0.04 mg / cm³, respectively. 2 0.06 mg / cm 2 and 0.23 mg / cm 2 The anode is made of NiFe material supported on nickel foam, while carbon paper is placed on the cathode side as a gas diffusion layer. The carbon paper, cathode, anode, PTFE gasket, and bipolar plate are assembled to form a membrane electrode assembly. The assembled membrane electrode assembly is subjected to AEMWE performance testing at 80 °C and with a 1 mol / L KOH electrolyte.

[0063] like Figure 8 As shown, PtRu 17 Cr 2.5 Nanocage at 1A / cm 2 At the given current density, the battery voltage is only 1.57 V, and its activity is significantly higher than that of Pt / C and PtRu. 10 Nanocage.

[0064] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the structure of the present invention or exceed the scope defined by the present invention, and all such modifications or additions should fall within the protection scope of the present invention.

Claims

1. A method for preparing a chromium-controlled PtRu-based nanocage catalyst, characterized in that, Includes the following steps: (1) A ruthenium precursor, a platinum precursor and a chromium precursor are introduced into a ZIF-8 metal-organic framework material, and a hollow porous nanocage structure multi-metal precursor / ZIF-8 composite is formed by reaction adsorption loading, wherein the mass ratio of the ruthenium precursor, platinum precursor, chromium precursor and ZIF-8 metal-organic framework material is (8~12):(0.5~5):(0.5~10):(16~18); (2) The multi-metal precursor / ZIF-8 complex is heat-treated in a hydrogen-containing reducing atmosphere to reduce Pt and Ru metal ions to the metallic state in situ, while Cr still exists in the form of oxides. At the same time, ZIF-8 decomposes to release zinc ions and forms a transition metal composite structure with Pt, Ru and Cr to obtain PtRuCrZnO intermediate. The heat treatment temperature is 300-350℃, the calcination time is 2-3 h, and the heating rate is 5-10℃ / min. (3) The ZnO in the PtRuCrZnO intermediate is removed by acid etching solution and the structure is reconstructed to obtain a chromium-controlled PtRu-based nanocage catalyst with a hollow porous cage morphology. The chromium-controlled PtRu-based nanocage catalyst is used to prepare the cathode material for alkaline anion exchange membrane water electrolysis.

2. The method for preparing the chromium-controlled PtRu-based nanocage catalyst according to claim 1, characterized in that: In step (1), the ZIF-8 metal-organic framework material is prepared as follows: zinc nitrate hexahydrate solution, 2-methylimidazole solution, and hexadecyltrimethylamine bromide solution are stirred and mixed evenly, and then allowed to stand to obtain ZIF-8 suspension.

3. The method for preparing the chromium-controlled PtRu-based nanocage catalyst according to claim 2, characterized in that: The mass ratio of zinc nitrate hexahydrate, 2-methylimidazole, and hexadecyltrimethylamine bromide is (0.3-0.4):(5-6):(0.016-0.018); the stirring speed is 350-450 rpm, the stirring time is 5-10 min, and the settling time is 2-3 h.

4. The method for preparing the chromium-controlled PtRu-based nanocage catalyst according to claim 1, characterized in that, In step (1): the reaction temperature is 50-80 °C and the reaction time is 2-4 h.

5. The method for preparing the chromium-controlled PtRu-based nanocage catalyst according to claim 1, characterized in that, In step (2): In the hydrogen-containing reducing atmosphere, the volume ratio of hydrogen to inert gas is (5%~10%): (90%~95%).

6. The method for preparing the chromium-controlled PtRu-based nanocage catalyst according to claim 1, characterized in that: In step (3), the acidic etching solution is a 0.5-1 mol / L hydrochloric acid solution, and the etching time is 20-40 min.

7. A chromium-controlled PtRu-based nanocage catalyst prepared by the method described in any one of claims 1 to 6.

8. The chromium-controlled PtRu-based nanocage catalyst according to claim 7, characterized in that: The chromium-regulated PtRu-based nanocage catalyst has a hollow porous cage structure and contains multi-metal synergistic active sites formed by Pt, Ru and Cr elements.

9. The application of the chromium-controlled PtRu-based nanocage catalyst as described in claim 7 in an alkaline anion exchange membrane water electrolysis system.

10. The application of the chromium-controlled PtRu-based nanocage catalyst according to claim 9 in an alkaline anion exchange membrane water electrolysis system, characterized in that: The PtRu-based nanocage catalyst is used to prepare electrode materials for the hydrogen evolution reaction at the cathode of water electrolysis.

Citation Information

Patent Citations

  • Alkaline electrocatalytic hydrogen evolution catalyst and preparation method and application thereof

    CN115110099A

  • Ruthenium nanocage used as alkaline fuel cell anode material and preparation method thereof

    CN115921848A